ELT worldwide - Universitas Negeri Makassar. Pascasarjana. Prodi Bahasa Inggris (English Language Education Graduate Program State University of Makassar, 2014)
Research articles of English Language Education practices around the world.
Keywords: English language : Study and teaching : Foreign speakers : Periodicals; English language : Study and teaching : Foreign speakers